Innovative Project-Based Learning Resources to Develop Critical Thinking Skills of Students in Basic Chromatography Instruction - Simalango, Meilin; Situmorang, Manihar (Universitas Negeri Medan, 2023)
Abstract: This study is a Research and Development (R&D) aimed at developing project-based innovative learning resources in the form of E-LKM on the topic of Chromatography with the goal of assessing its effectiveness in improving critical thinking skills and students' learning outcomes. The development method used is the ADDIE model with 3 cycles of implementation stages. The development results indicate that the project-based E-LKM has an average total feasibility score of BSNP = 3.85, categorized as very feasible, and an N-gain score of 0.72, equivalent to a percentage of 72%, indicating high effectiveness. During field trials, there was an increase in the average scores M4 > M3 > M1, indicating an improvement in students' abilities in the Chromatography teaching process. Hypothesis testing results show a significant difference between students' learning outcomes before and after using the developed project-based innovative learning resources. Additionally, based on the correlation calculation between critical thinking skills and students' learning outcomes, it was found that there is a significant positive correlation. Thus, it can be concluded that project-based innovative learning resources are effective in improving students' learning outcomes, and there is a correlation between critical thinking skills and students' learning outcomes in the context of teaching chromatography.Keywords: Innovative Learning Resources, E-LKM (Electronic Learning Module), PjBL (Project-Based Learning), Critical Thinking Skills, Chromatography.